Influence of phase and clock synchronization errors on the noise immunity of coherent reception of signals with quadrature amplitude modulation - G. V. Kulikov; A. A. Lelyukh; E. V. Batalov (Российский технологический журнал, 2021)
Signals with quadrature amplitude modulation (QAM) is widely used for high-speed transmission of information in many radio systems and, in particular, in digital television systems. In the receiver, which is part of the transceiver equipment of such systems, there is a block for the formation of reference oscillations and a clock synchronization block. Due to hardware instabilities and propagation conditions, phase and clock errors may occur, which cause additional errors during demodulation of the received signal, and which can significantly impair the noise immunity of the reception. The paper investigates the effect of phase and clock synchronization errors on the noise immunity of coherent reception of QAM signals. Using the methods of statistical radio engineering, the parameters of the distributions of processes in the receiver are obtained and the probability of bit error is estimated. The dependences of the probability of bit error on the magnitude of the phase error in the formation of the reference oscillations and on the relative displacement of the clock moments, as well as on the signal-to-noise ratio, are obtained. It is shown that these errors can greatly reduce the noise immunity of the reception, and with an increase in the positioning of the signals, this effect increases. If we assume that the admissible reception energy loss is 0.5 dB due to each of these errors, then the allowable phase error is from ~3° at M = 4 to ~1° at M = 64, and the allowable clock synchronization error, respectively, is from ~5% at M = 4 to ~2% at M = 64. To provide more stringent requirements for the magnitude of losses, the requirements for the indicated errors increase significantly.